Plantago lagopus extract as a green fungicide induces systemic resistance against Rhizoctonia root rot disease in tomato plants - Behiry, Said I.; Al-Askar, Abdulaziz A.; Soliman, Seham A.; Alotibi, Fatimah O.; Basile, Adriana; Abdelkhalek, Ahmed; Elsharkawy, Mohsen Mohamed; Salem, Mohamed Z. M.; Hafez, Elsayed E.; Heflish, Ahmed A. (Frontiers in Plant Science, 2022)
Extensive use of chemical control agents and fungicides typically leads to numerous risks to human health and the environment. Using plant extracts as natural substances represents a dual key for the environment and sustainable food production, as it reduces the input of synthetic pesticides into the environment and/or controls plant pathogens. For the first time, a Plantago lagopus ethanolic extract has been characterized and evaluated for its protective and curative effects against Rhizoctonia solani in tomato plants. The results showed that P. lagopus extract (10 μg/ml) completely inhibited R. solani mycelial growth in vitro. At 20 days of post fungal inoculation, the results demonstrated that using P. lagopus extract (100 μg/ml) in vivo enhanced tomato plant growth by significantly increasing shoot and root parameters in protective and curative treatments. Furthermore, the protective and curative treatments significantly reduced the disease index by 18.66 and 38.66%, respectively. Induction of systemic resistance with upregulation of PR-1 and PR-2 and a significant increase in the transcriptional levels of PR-3 and CHS in all P. lagopus extract-treated tomato plants were reported compared to untreated plants. HPLC analysis showed that the most common polyphenolic components detected in P. lagopus extract were rutin (74206.3 mg/kg), naringenin (2388.74 mg/kg), quercetin (1249.13 mg/kg), and p-hydroxybenzoic acid (1035.87 mg/kg). In addition, the ellagic acid (798.47 mg/kg), vanillic acid (752.55 mg/kg), catechol (648.89 mg/kg), cinnamic acid (332.51 mg/kg), ferulic acid (296.32 mg/kg), benzoic acid (295.95 mg/kg), and chlorogenic acid (116.63 mg/kg) were also reported. Our study is the first to show that P. lagopus extract can help plants fight off R. solani fungal infection. Furthermore, the findings imply that using the P. lagopus extract as a natural biocontrol agent could be a sustainable strategy to manage plant fungal diseases.